Gendering War Talk. - Cooke, Miriam G. (Princeton legacy library., 2014)
In a century torn by violent civil uprisings, civilian bombings, and genocides, war has been an immediate experience for both soldiers and civilians, for both women and men. But has this reality changed our long-held images of the roles women and men play in war, or the emotions we attach to violence, or what we think war can accomplish? This provocative collection addresses such questions in exploring male and female experiences of war--from World War I, to Vietnam, to wars in Latin America and the Middle East--and how this experience has been articulated in literature, film and drama, his.